Wnt-3a and Dvl Induce Neurite Retraction by Activating Rho-Associated Kinase - Kishida, Shosei (American Society for Microbiology, 2004)
Dvl is a key protein that transmits the Wnt signal to the canonical β-catenin pathway and the noncanonical planar cell polarity (PCP) pathway. We studied the roles of Rho-associated kinase (Rho-kinase), which is activated by Dvl in the PCP pathway of mammalian cells. The expression of Dvl-1, Wnt-1, or Wnt-3a activated Rho-kinase in COS cells, and this activation was inhibited by the Rho-binding domain of Rho-kinase. The expression of Dvl-1 in PC12 cells activated Rho and inhibited nerve growth factor (NGF)-induced neurite outgrowth. This inhibition was reversed by a Rho-kinase inhibitor but not by a c-Jun N-terminal kinase inhibitor. Dvl-1 also inhibited serum starvation-dependent neurite outgrowth of N1E-115 cells, and expression of the Rho-binding domain of Rho-kinase reversed this inhibitory activity of Dvl-1. Dvl-1 mutants that did not activate Rho-kinase did not inhibit the neurite outgrowth of N1E-115 cells. Furthermore, the purified Wnt-3a protein activated Rho-kinase and inhibited the NGF-dependent neurite outgrowth of PC12 cells. Wnt-3a-dependent neurite retraction was also prevented by a Rho-kinase inhibitor and a Dvl-1 mutant that suppresses Wnt-3a-dependent activation of Rho-kinase. These results suggest that Wnt-3a and Dvl regulate neurite formation through Rho-kinase and that PC12 and N1E-115 cells are useful for analyzing the PCP pathway.